Hydrogen induced degradation: a possible mechanism for light- and elevated temperature- induced degradation in n-type silicon - Chen, D; Hamer, PG; Kim, M; Fung, TH; Bourret-Sicotte, G; Liu, S; Chan, CE; Ciesla, A; Chen, R; Abbott, MD; Hallam, BJ; Wenham, SR (Elsevier, 2018)
In this work, we demonstrate a form of minority carrier degradation on n-type Cz silicon that affects both the bulk and surface related lifetimes. We identify three key behaviors of the degradation mechanism; 1) a firing dependence for the extent of degradation, 2) the appearance of bulk degradation when wafers are fired in the presence of a diffused emitter and 3) a firing related apparent surface degradation when wafers are fired in the absence of an emitter. We further report a defect capture cross-section ratio of σn/σp = 0.028 ± 0.003 for the defect in n-type. Utilizing our understanding of light and elevated temperature induced degradation (LeTID) in p-type silicon, we demonstrate that the degradation behaviors in both n-type and p-type silicon are closely correlated. In light of numerous reports on the involvement of hydrogen, the potential role of a hydrogen-induced degradation mechanism is discussed in both p- and n-type silicon, particularly in relation to the diffusion of hydrogen and influence of hydrogen-dopant interactions.